APLIKASI LASER KONTINYU DALAM ANALISIS MATERIAL BERDASARKAN CRATER YANG DIHASILKAN - emy alemmita br tarigan (Saintia Fisika, 2013)
The interaction of laser have been done with a particular material. The type of laser that been used is continue laser. One of the laser is CO2 laser  with wavelength of 10.6 nm and the CO2 laser that we used has power ± 8 watt.. Interaction process is done at the focal point and defokus each laser. In CO2 laser the focal point is 5 cm and the defocus is 7 cm in front of the lens. In the process of laser interaction with the material, the most influential physical properties of the material is the melting point of the material. The melting point of silicon rubber, which 1410oC is higher than acrylic material which has 160oC and the plastic has 115-125 oC. The higher is needed the melting point of the material, the greater and the longer interaction time. The size of the resulting crater diameter depends on the laser output power, the time, the focal point of the laser defocus and the type of materials used. So it is known that silicon rubber requires the highest power and longest time so that size is wider in diameter than the plastic and acrylic materials.